Evaluation of the performance of private hospitals from the point of view of the beneficiaries (A field Study in the private Sector hospitals in Baghdad) - hanafi, basil (Iraqi National Journal of Nursing Specialties, 2005)
Objectives: This Paper is an attempt to evaluate the services provided by the private hospitalsand to identify the strength and weakness intheir performance The results can be utilized in stating conclusion and recommendations to improveand activate the role of private medical sector in society .Methodology: A questionnaire has be designed for this purpose and distributed to ( 132 ) beneficiariesmostly from Baghdad private hospitals .Results: The paper has come out with many important results . Among These are the following :* these who benefit from services provided by private hospitals believe that the good performance ofsuch hospital is not due to the medical services alone but also to scientific aspects .* The results also show that the simple satisfaction factors on the lack of integrated services and not onthe prices of such services .Key words : ( performance, evaluation, private hospitals )